The impact of driving time on participation in colorectal cancer screening with sigmoidoscopy and faecal immunochemical blood test. (October 2022) - Berthelsen, Mona; Berstad, Paula; Randel, Kristin R.; Hoff, Geir; Natvig, Erik; Holme, Øyvind; Botteri, Edoardo
Abstract: Background: High participation rates are important for a colorectal cancer (CRC) screening programme to be effective. Having a long travelling distance to screening centres may impede participation. Methods: We analysed the association between driving time from home address to screening centre and participation among individuals invited to screening with faecal immunochemical test (FIT) (n = 68, 624) or sigmoidoscopy (n = 46, 076) in a randomized trial in Norway in 2012–17. Two screening centres were involved. We fitted multiple logistic regression models, adjusted for demographic, socioeconomic and health characteristics, and reported odds ratios (OR) with 95% confidence intervals (CI). Results: Participation rates were 58.9 % (n = 40, 445) for FIT and 51.9 % (n = 23, 911) for sigmoidoscopy. In sigmoidoscopy, participation was 56.9 % and 47.9 % in those living < 20 and > 60 min by car from the screening centres, respectively. For each 10 min driving time increase, OR for participating in sigmoidoscopy screening was 0.93 (95 % CI 0.91–0.95). There was a significant difference between the two screening centres (p-value for heterogeneity <0.001). Participation in FIT screening were 61.2 % and 57.1 % in those with < 20 and > 60 min driving time, respectively, and the OR was 0.98 (95 % CI 0.96–0.99) for each 10 min increase (heterogeneity between screening methods, P-value <0.001). Among those with a positive FIT, compliance to colonoscopy was higher in those living < 20 compared to > 60 min from the centres (95.1 % vs. 92.9 %, respectively, OR 0.86; 95 % CI 0.77–0.93 for each 10 min increase). Conclusions: Driving time to screening centre was a significant predictor of participation, mainly in sigmoidoscopy. There were local differences in the impact of driving time on participation. Driving time also affected compliance to colonoscopy after a positive FIT. When planning a CRC screening programme, one should consider offering people living far from screening sites special assistance to facilitate their participation. Highlights: Driving time to screening centre impacted participation in CRC screening. Increase of 10 min corresponded to a 7% decrease in sigmoidoscopy participation. This association was significantly different between the two screening centres. Colonoscopy acceptance after positive FIT decreased by 14% every 10 additional min.